Cytotoxic, thrombolytic, membrane stabilizing and anti-oxidant activities of Hygrophila schulli (Bangladesh Journal of Pharmacology, 2015)
The crude methanol extract of Hygrophila schulli and its petroleum ether, chloroform, ethyl acetate and aqueous soluble Kupchan partitionates were investigated for in vitro cytotoxic, thrombolytic, membrane stabilizing and anti-oxidant activities. In the brine shrimp lethality bioassay, the petroleum ether soluble extract of H. schulli showed significant cytotoxicity (LC50 = 0.1 µg/mL and LC90 = 15 µg/mL) as compared to vincristine sulfate (LC50 = 0.4 µg/mL and LC90 = 9 µg/mL). Among all the partitionates, chloroform soluble fraction demonstrated the highest thrombolytic activity with 10.5% clot lyses. Moreover, in hypotonic- and heat-induced conditions, the chloroform soluble extractive inhibited hemolysis of human erythrocyte by 113.7% and 14.3%, respectively as compared to 71.9% and 42.2% demonstrated by standard acetylsalicylic acid. On the other hand, in anti-oxidant activity test, chloroform soluble fraction revealed mild antioxidant activity (IC50 = 195.1 µg/mL) as compared to standard tert-butyl-1-hydroxytoluene (IC50 = 27.5 µg/mL).